Experimental and parametric investigation on industrial lubricants transformation to synthetic fuels for stationary compression ignition engines - Tewfik Leftas; Mohamed Bencherif; Abdelouahed Benzerdjeb; Nasreddine Larbes; Sofiane Mimoun; Amel Kaced (Journal of Engineering and Applied Science)
Abstract This paper presents an experimental investigation of chemical transformation of industrial lubricants into oxygenated synthetic fuels and their use in a diesel engine. A catalytic extraction is achieved by transesterification using methanol and potassium hydroxide. Industrial oils are mainly Tiska 32, Tiska 46, Tiska 68, Torba 32, Torba 46, Torba 68, Torada 32, and Tilia B233. In addition, biofuel extracted from waste cooking oil and conventional diesel fuel have been taken for comparison. Physical and chemical properties of both biofuel and synthetic fuels as well as their blends are measured, presented, and discussed. Those properties are liquid density and viscosity, acidity number, and flash point. Gas chromatography-mass spectroscopy has been done in order to determine synthetic fuels and biofuel composition. A first look indicates that the oxygenated fuels have low acidity number, but their viscosities are quite high. A careful examination, in accordance with the limitations and regulations, leads us to direct use in the engine with a maximum blending ratio of 50%. A set of three blends with 15%, 30%, and 45% of each synthetic fuel and the biofuel are tested on a diesel engine in order to compare performances, fuel consumption, and NOx emissions. The results are compared with those obtained when the engine is powered with conventional diesel fuel.